Rediseño de un parque comunitario aplicando eco arquitectura en la Cooperativa El Bosque del cantón Durán - Aymar Freire, David Alejandro (2025)
In Durán, the current urban public spaces present flaws in architectural and functional aspects, in addition to the infrastructure of their equipment and furniture in poor condition, which has affected the comfort and stay conditions in public spaces such as urban parks, this being a factor. determining factors for people not wanting to use them. The proposal to redesign an urban park with eco-architecture criteria in the El Bosque del Cantón Durán Cooperative aims to improve accessibility for users focused on comfort, safety and social inclusion. The bases of eco-architecture focus on the pillars of territorial sustainability, involving nature as the driving force for the development of sites of social dynamism, equipment and accessories within a public space. Likewise, important factors such as easy accessibility and connectivity, the incorporation of vegetation, security and comfort are considered to ensure a pleasant space. In the same way, active recreation areas are incorporated, such as sports fields, children's games and outdoor exercise. Passive recreation areas such as interactive trails and rest areas provide relaxation. In conclusion, the contribution of eco-architecture towards the redesign of the community park of the Cooperativa el Bosque del Cantón Durán provides a diverse urban image and a development focused on the sustainability of the landscape and the environment that improves the biophysical and urban conditions of the sector by expanding thus quality of life factors at risk such as the urban green index or care for the biodiversity of landscapes.